2018
DOI: 10.1002/anie.201805099
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of 14C‐Labeled Graphene to 14CO2 in the Shoots of a Rice Plant

Abstract: This study focused on using carbon-14-labeled few-layer graphene (FLG) to determine its uptake, distribution, transformation, and depuration in rice plants. After 7 d hydroponic exposure to FLG suspension at 250 μg L , roots accumulated 694.8 mg kg graphene and shoots had 53.7 mg kg graphene from intra-plant translocation. FLG could likely pass through the cell wall and membrane and enter the chloroplast in the shoots. After 14 days of depuration, only about 15 % of the accumulated FLG were eliminated into the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 37 publications
(17 reference statements)
2
35
0
Order By: Relevance
“…Conversely, GO mainly accumulated in the roots and low levels in leaves. Besides root accumulation and translocation from root to shoot, Huang et al (2018) further discovered that ~9% of the accumulated FLG was degraded to CO 2 in the rice plant, and that the hydroxyl radical in the leaf played an important role in degrading FLG. Earlier studies have demonstrated that CO 2 was the final product of the complete enzymatic catalyzed oxidation of GO (Kotchey et al, 2011), and H 2 O 2 was a key component of this degradation process (Xing et al, 2014).…”
Section: Phytotoxicity Of Gfnsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, GO mainly accumulated in the roots and low levels in leaves. Besides root accumulation and translocation from root to shoot, Huang et al (2018) further discovered that ~9% of the accumulated FLG was degraded to CO 2 in the rice plant, and that the hydroxyl radical in the leaf played an important role in degrading FLG. Earlier studies have demonstrated that CO 2 was the final product of the complete enzymatic catalyzed oxidation of GO (Kotchey et al, 2011), and H 2 O 2 was a key component of this degradation process (Xing et al, 2014).…”
Section: Phytotoxicity Of Gfnsmentioning
confidence: 99%
“…Compared to assessing their toxicity, the uptake, transport, distribution, and degradation of GFNs within plants remains poorly understood (Huang et al, 2018). Their transformation pathways and fate in water/soil-plant systems requires additional research, which will contribute to prevention of environmental risks.…”
Section: Problems and Prospectsmentioning
confidence: 99%
“…Kah et al (2017) reviewed the sorption of ionic and ionizable organic compounds (IOCs) on carbonaceous materials (activated carbon, biochar, carbon nanotubes and graphene) and concluded that the adsorption of IOCs was mainly dominated by electrostatic interactions, electron donor-acceptor interactions, charge-assisted hydrogen bonds and cation-π assisted π-π interactions. They also suggested the possible transformation of IOCs may occur through different mechanisms, which should receive attention in the context of environmental remediation (Hu et al 2019;Huang et al 2018;Zhao et al 2019a). Yang et al (2019a) reviewed different kinds of heavy metal ions on carbon materials and the surface introduction of oxygen, nitrogen and sulfur functional groups onto carbon materials to improve the sorption capacities of metal ions.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, in this study, the comparison with MICA highlighted that FLG can be considered as safe as a naturally occurring planar NM, not uncommon in soil particulate matter. However, before excluding FLG from the ecotoxicologically relevant substances for seed plants, biodistribution and transformation in the plant body [ 78 , 79 ] still need to be thoroughly investigated.…”
Section: Discussionmentioning
confidence: 99%